Peran Probiotik Terhadap Kadar Zonulin pada Penderita Obesitas - Rizkia, Chaula Putri (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
The prevalence of obesity is increasing worldwide and is considered as epidemic. According to the 2018 Riskesdas data, the obesity rate in Indonesia has increased to 35.4% compared to 2007. Obesity is a risk factor for metabolic diseases due to chronic inflammatory conditions. This is associated with increased permeability of the intestinal wall which is characterized by increased levels of zonulin. Probiotics are known to reduce zonulin levels and improve intestinal integrity in obesity.